COMMON FIXED POINT THEOREMS FOR PAIRS OF SELF-MAPPINGS ON (3; 2)-W-SYMMETRIZABLE SPACES - Dimovski, Tomi; Dimovski, Dončo (Matematichki Bilten, 2023)
In this paper, we prove the existence and the uniqueness of a fixed point for pairs of self-mappings on \((3, 2)\)-\(W\)-symmetrizable spaces using self-mappings similar to \(T_F\) contractions in ordinary metric spaces, and we obtain two corollaries.